Uranium in the Aquatic Environment 2002
DOI: 10.1007/978-3-642-55668-5_68
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Uranium Fixation by Zero Valent Iron: The Importance of Co-precipitation

Abstract: The coprecipitation of U (VI) with iron corrosion products from aqueous solutions by zero valent iron was investigated. The evidence of coprecipitation was demonstrated by conducting experiments with well characterized scrap iron, pyrite and a mixture of both materials with experimental durations of up to four months. Results indicate that under anoxic conditions only less than one tenth of the immobilized U(VI) was associated with the surface of scrap iron, whereas the remaining amount is entrapped in aging c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…It was shown that U(VI) removal is accompanied by a decrease of aqueous iron concentration and that Fe(II) was the dominating iron species under the experimental conditions. [21] In the pH range of observed U(VI) removal (4.0 to 4.4), iron corrosion should mostly occur without H 2 production, [32,33] and U(VI) reduction trough ZVI should have been very favorable because ZVI surface is neither covered by iron corrosion products nor H 2 bubbles. [12] Instead of that, U(VI) removal occurred only very slowly (18 % at day 43 and 94 % at day 94) and was accompanied by a decreased of iron corrosion, suggesting that U(VI) removal is the result of U(VI) entrapment in the matrix of precipitating iron hydroxide.…”
Section: (System I) "Fes 2 (D 2 )" (System Ii) "[Zvi + Fes 2 (D 2 )mentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that U(VI) removal is accompanied by a decrease of aqueous iron concentration and that Fe(II) was the dominating iron species under the experimental conditions. [21] In the pH range of observed U(VI) removal (4.0 to 4.4), iron corrosion should mostly occur without H 2 production, [32,33] and U(VI) reduction trough ZVI should have been very favorable because ZVI surface is neither covered by iron corrosion products nor H 2 bubbles. [12] Instead of that, U(VI) removal occurred only very slowly (18 % at day 43 and 94 % at day 94) and was accompanied by a decreased of iron corrosion, suggesting that U(VI) removal is the result of U(VI) entrapment in the matrix of precipitating iron hydroxide.…”
Section: (System I) "Fes 2 (D 2 )" (System Ii) "[Zvi + Fes 2 (D 2 )mentioning
confidence: 99%
“…Although it has been recognised that the formation of iron oxide or hydroxide over the surface may decrease the reactivity of ZVI materials, available information of the effects of oxide-films on the reductive capacity of ZVI materials results largely from well-mixed batch experiments [Huang et al 2003, Johnson et al 1998, Kim & Carraway 2000, Lin & Lo 2005, Ritter et al 2002, Weber et al 1996 . However, this experimental procedure (shaken or stirred batch experiments) may be inconsistent with groundwater environments (flow velocities 5-50 cm/day) where iron precipitates are continuously generated on ZVI surface, probably forming a reactive physical barrier to several contaminants [Devlin et al 1998, Devlin & Allin 2005, Mishra & Farrell 2005, Noubactep et al 2001 . Consequently, it is important to investigate the mechanism of contaminant removal by ZVI under not shaken conditions, where generated corrosion products remain on the iron surface and compete with ZVI for contaminant removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,23,24] This purpose is complicated in short term laboratory experiments by two key factors that have been found to influence the interaction of ZVI materials with contaminants: the oxidation state of the iron surface and the presence of corrosion products on it. [23,25,26] .…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of the pH is due to pyrite oxidation (Bain et al 2001, Williamson & Rimstidt 1994) that normally increases the solubility of U (Noubactep et al 2002). Under the experimental conditions (neutral pH, oxic) however dissolved Fe 2+ ions from pyrite lead upon oxidation by dissolved oxygen to Fe(OH) 3(am) precipitates that are excellent sorbents for U (Ho & Miller 1986, Jambor & Dutrizac 1998.…”
Section: Effect Of the Additive Materialsmentioning
confidence: 96%